ANALISIS KOMPETENSI PEGAWAI DI SEKRETARIAT DAERAH KOTA CIREBON (Studi Kasus Perbedaan Kompetensi Pegawai Laki-laki dan Perempuan) - Vina Nushrotul Jannah; Ipik Permana; Moh Taufik Hidayat (Universitas Swadaya Gunung Jati, 2015)
ABSTRACT This Research about Competency Differences between male employees and female employees (Study Productivity of Gender).The problem is the competence of employees in Regional Secretariat of Cirebon city is not optimal, male employee competence expected to be lower than the competence of female employees.The hypothesis of the study is: